2017
DOI: 10.1002/asia.201700405
|View full text |Cite
|
Sign up to set email alerts
|

Ambient‐Pressure Stabilization of β‐GdB3O6 by Doping with Bi3+ and Color‐Tunable Emissions by Co‐Doping with Tb3+ and Eu3+: The First Photoluminescence Study of a High‐Pressure Polymorph

Abstract: Rare-earth borates are good candidates for optical applications. To date, however, the high-pressure/high-temperature technique has produced a large number of novel borates with optical properties that have rarely been investigated due to the severe problem of substantial defects. We targeted the high-pressure polymorph of β-GdB O and synthesized three solid solutions of β-Gd Bi Tb B O (0≤x≤0.75), β-Gd Bi Eu B O (0≤y≤0.75), and β-Gd Bi Tb Eu B O (0≤z≤0.05) by using typical solid-state reactions at 820 °C. Here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
(128 reference statements)
0
3
0
Order By: Relevance
“…There are some single-composition white light emission phosphors materials can be obtained at near ultra-violet(n-UV), such as Ca 9 Gd(PO 4 ) 7 :Eu 2+ , Mn 2+ [25], NaBaBO 3 :Dy 3+ , K + [26], and Sr 3 Y(PO 4 ) 3 :Dy 3+ [27]. However, many materials need UV excitation under 300 nm to realize white light emission, such as Y(P,V)O 4 :Dy 3+ [28], β-GdB 3 O 6 :Bi 3+ , Tb 3+ , Eu 3+ [29], LaNbO 4 :Dy 3+ [30], and LuNbO 4 :Dy 3+ [31]. Taking LuNbO 4 :Dy 3+ as example, the excitation peak of LuNbO 4 :Dy 3+ phosphors centered in 261 nm.…”
Section: Introductionmentioning
confidence: 99%
“…There are some single-composition white light emission phosphors materials can be obtained at near ultra-violet(n-UV), such as Ca 9 Gd(PO 4 ) 7 :Eu 2+ , Mn 2+ [25], NaBaBO 3 :Dy 3+ , K + [26], and Sr 3 Y(PO 4 ) 3 :Dy 3+ [27]. However, many materials need UV excitation under 300 nm to realize white light emission, such as Y(P,V)O 4 :Dy 3+ [28], β-GdB 3 O 6 :Bi 3+ , Tb 3+ , Eu 3+ [29], LaNbO 4 :Dy 3+ [30], and LuNbO 4 :Dy 3+ [31]. Taking LuNbO 4 :Dy 3+ as example, the excitation peak of LuNbO 4 :Dy 3+ phosphors centered in 261 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, Bi 3+ can also be used as a blue-emitting center to combine with Tb 3+ and Eu 3+ ions to obtain single-composition white phosphors, and some reported examples include b-GdB 3 O 6 :Bi 3+ , Tb 3+ , Eu 3+ , Ca 3 ZrSi 2 O 9 :Bi 3+ , Tb 3+ , Eu 3+ , Gd 2 MoB 2 O 9 :Bi 3+ , Tb 3+ , Eu 3+ and NaYGeO 4 :Bi 3+ /Tb 3+ /Eu 3+ . [29][30][31][32] However, doping with three ions such as Bi 3+ , Tb 3+ , and Eu 3+ can lead to complicated energy transfer, so tuning to accurate white color remains still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…While under exposure to UV light, YBO 3 : Tb 3+ displays the typical green emission at~546 nm ( 5 D 4 → 7 F 5 transition of Tb 3+ ), and color-tunable photoluminescence can be found in solid solution phosphor of Y/Tb/Eu ternary system through an efficient energy transfer from Tb 3+ to Eu 3+ ions [18][19][20]. Recently, it was reported that doping Bi 3+ in rare-earth borates could effectively manipulate the synthetic/thermal stable temperature [21]. In addition, further doping Bi 3+ in Y/Tb/Eu ternary system is a good idea to take advantage of the sensitization effect of Bi 3+ to obtain a single-phase phosphor with color-tunable and greatly improved emission by manipulating the doped concentrations of Bi 3+ , Eu 3+ , and Tb 3+ in YBO 3 [22].…”
Section: Introductionmentioning
confidence: 99%